On multi attribute decision making methods: Prioritizing information security controls - AL-Safwani, Nedher; Hassan, Suhaidi; Katuk, Norliza (AENSI Publications, 2014)
This study deals with the problem of prioritization of Information Security Controls where most organizations aim to address and manage them effectively. Current information security analysis methods lack a quantitative approach and mostly depend on subjective judgments of information security experts.Although, expert opinions assist organizations in measuring the effectiveness of security controls, the subjective judgments may yield different results.Hence, a more objective approach that can be quantified is an alternative.This study implements multiple attribute decision-making concepts for prioritizing and selecting security controls using Hierarchical Adaptive Weighting (HAW) and Simple Adaptive Weighting (SAW).The results of these analysis methods are reported and compared.